Comprehensive Guidance and Counseling in Improving The Resilience of Students - Arsini, Yenti; Ahman, Ahman; Suganhi, Nani; Nurhudaya, Nurhudaya (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
Literatur examines resilience as an individual’s endurance in dealing with, responding to, and overcoming obstacles, challenges, stresses, and traumatic experiences. It is a negative view because resilience is viewerd only as a response to the condition of entropy. The facts show that the stressful challenges to the individual happen at all times, throughout the life of the individual, in a variety of events such as natural disasters, riots conflicts, wars, and the atmosphere of life that seeks sustainability and adequate decisions. Comprehensive Guidance and Counseling (CGC) adopts a positive view in assessing resilience and sees and understands resilience as a development. Resilience is viewed as a process and product, an indidual sustainability condition. Resilience is seen as a competence in adaptable adjustment, a healthy and open person, independence in making decisions and responsibilities, a fight for achievement, and a peaceful person who encourages the development of authentic and tough personality. Resilience is not the end point of individual endurance and resilience development but is a bynamic and life-long developmental process that always adapts to environmental changes, dynamics, and challenges. Resiliensi is a skill and individual competence that must be developed as long-term behavior. CGC as a development-oriented approach views resilience as one of the various aspects of student development, as a psychohygiene condition that should be a general purpose aspect of education and guidance that becomes the basis of authentic and tough personality development. The series of research and concepts on adeguacy of adjustment, productive personality, health personality, academic hardness, and peacefulness have high incisions with resilience, which are examined in this paper